DAS FRONTEIRAS INSTITUCIONAIS À MOBILIZAÇÃO SOCIAL: intervenções no processo de doação e transplante de órgãos entre tecidos - Lima, Heloisa Rosário Furtado Oliveira (2015)
In Maranhao, donation, organs and tissues transplatation process began in 2000 with the creation of Transplant Center and the execution of the first kidney and cornea transplant. However, organization, operation and evolution of this service needs new perspectives and practices to raise the number of organs and tissues donations. Before that, we asked: which instruments, tools and strategies can be used to increase the number of potential and effective donors of organs and tissues in Maranhão? The research objective was building innovative measures aimed at increasing notifications, donations and transplants in Maranhão from the active participation of the actors involved in the donation, capture and organ transplantation process. The investigation was guided by Convergent Care Research, with a qualitative approach, and it involved 50 participants between five hospitals technicians (03 public and 02 private) from services related to donation and organ transplantation process (Intra-Hospital Transplant Commissions, Eye Bank, Transplantation Center, Intensive Care and Urgent and Emergency Services). It also involved managers of these hospitals and from Secretaria Municipal de Saúde de São Luís MA (health's secretary, control superintendent, beds evaluation, audit and regulation, beds Regulation Center coordinator) and Prosecutor's Office. Wheel conversations, focus groups and individual meetings were strategies to data collection, and it had identified limitations and build strategies and interventions to donation and organ transplantation process. Interventions were product of participant s collective work and it has been organized in three dimensions: institutional; technical-professional and social mobilization. As a result of interventions, we had the following changes in organ and tissue donation s process from Maranhão: increase in deaths and brain death notifications; more hospitals closing brain death protocol; increase in closed brain death protocols; completion time s reduction in brain death protocol; greater interaction between Transplantation Center and notifiers hospitals; Intra-Hospital Transplant Commissions implementation and reactivation; cooperative and collaborative work between Central, Eye Bank and the Intra-Hospital Transplant Commission; increase in donations and transplants. The interventions produced positive results in donation and cornea and kidney s transplants. From 2013 to 2014, Maranhão occupied the 19th position in kidney transplant and 21th position in cornea transplant. Advances were achieved by research in May 2015, so the state began occupying the 17th position in the kidney transplant and the 18th position in cornea transplant. It focused effectively on Maranhão performance in national ranking of kidney and cornea transplant. The disruption of institutional borders via interventions in the process of donation and transplant of organs and tissues by social mobilization represented a significant evolution in the increase in the number of donations and, consequentely, of transplants of organs and tissues.